Attitudes and perceptions of next-of-kin/loved ones toward end-of-life HIV cure-related research: A qualitative focus group study in Southern California - Javadi, Sogol S. (PLoS One, 2021)
As end-of-life (EOL) HIV cure-related research expands, understanding perspectives of participants’ next-of-kin (NOK) is critical to maintaining ethical study conduct. We conducted two small focus groups and two one-on-one interviews using focus group guides with the NOK of Last Gift study participants at the University of California, San Diego (UCSD). Participating NOK included six individuals (n = 5 male and n = 1 female), including a grandmother, grandfather, partner, spouse, and two close friends. Researchers double-coded the transcripts manually for overarching themes and sub-themes using an inductive approach. We identified six key themes: 1) NOK had an accurate, positive understanding of the Last Gift clinical study; 2) NOK felt the study was conducted ethically; 3) Perceived benefits for NOK included support navigating the dying/grieving process and personal growth; 4) Perceived drawbacks included increased sadness, emotional stress, conflicted wishes between NOK and study participants, and concerns around potential invasiveness of study procedures at the EOL; 5) NOK expressed pride in loved ones’ altruism; and 6) NOK provided suggestions to improve the Last Gift study, including better communication between staff and themselves. These findings provide a framework for ethical implementation of future EOL HIV cure-related research involving NOK.